The Urgency of Pesantren Managerial Reconstruction in the Era of Globalization - Fauzan Fauzan; Moh. Dannur; Samsul AR; Artamin Hairit; Ahmad Zaini (Al-Abshar: Journal of Islamic Education Management, 2025)
The existence of pesantren as educational institutions faces challenges from rapid changes in the increasingly complex era of globalization. Traditional pesantren with individual leadership models find it difficult to develop due to non-collective development approaches. Modern pesantren face moral crisis challenges due to insufficient internalization of moral values in pesantren activities sourced from religious texts. Combined traditional-modern pesantren face dilemmatic challenges in maintaining traditional values while responding to changing times, causing pesantren to tend to prioritize technical management while neglecting mastery of classical Islamic texts (kitab kuning). These challenges must be responded to responsively by implementing pesantren managerial innovations to maintain sustainability amid societal demands. Pesantren managerial innovation is expected to become a strategic step in maintaining traditional pesantren values and evolving with modernity, without losing the indigenous identity of pesantren. This research uses qualitative methods with a literature review approach analyzing various relevant literature sources. This study aims to analyze the importance of pesantren managerial transformation by integrating traditional leadership models with modern management principles. Pesantren managerial transformation can use strategic management concepts in achieving pesantren goals including visionary planning, measurable goal setting, and continuous evaluation.